2016
DOI: 10.1259/bjr.20150357
|View full text |Cite
|
Sign up to set email alerts
|

A review of percutaneous techniques for low back pain and neuralgia: current trends in epidural infiltrations, intervertebral disk and facet joint therapies

Abstract: Low back pain and neuralgia due to spinal pathology are very common symptoms debilitating numerous patients with peak prevalence at ages between 45 and 60 years. Intervertebral discs and facet joints act as pain sources in the vast majority of the cases. Diagnosis is based on the combination of clinical examination and imaging studies. Therapeutic armamentarium for low back pain and neuralgia due to intervertebral discs and/or facet joints includes conservative therapy, injections, percutaneous therapeutic tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 73 publications
2
41
0
6
Order By: Relevance
“…Back pain has various causes, and cytokine and inflammatory substances associated with disk ruptures are removed during the surgery, which may partially explain why improvements in postoperative back pain were observed in the two groups. 33,34 Epidural and perineural scar tissue often make repeated OLM more difficult and increase the risk of nerve root injuries that may cause clinical sequelae and poor clinical outcomes. 7,35 In previous studies, permanent foot drop and persistent voiding disturbances were reported, and there was one case of foot drop and seven cases of transient sensory change in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Back pain has various causes, and cytokine and inflammatory substances associated with disk ruptures are removed during the surgery, which may partially explain why improvements in postoperative back pain were observed in the two groups. 33,34 Epidural and perineural scar tissue often make repeated OLM more difficult and increase the risk of nerve root injuries that may cause clinical sequelae and poor clinical outcomes. 7,35 In previous studies, permanent foot drop and persistent voiding disturbances were reported, and there was one case of foot drop and seven cases of transient sensory change in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These joints have a large amount of free and encapsulated nerve endings 52 that activate nociceptive afferents and that are also modulated by sympathetic efferent fibers 53 . Lumbar zygapophyseal or “facet” joint pain has been estimated to account for up to 30% of CLBP cases 54 , with nociception originating in the synovial membrane, hyaline cartilage, bone, or fibrous capsule of the facet joint 55 .…”
Section: Type Of Spinal Pain According To Pain Generatormentioning
confidence: 99%
“…Imaging guidance is a prerequisite for correct canula placement; fluoroscopy and ultrasound are the most commonly used modalities [8][9][10]. Cone beam fluoroscopy can provide CT like 3D reconstructions acting as a problem solver in obese patients or other difficult situations; alternatively navigation and reconstruction systems may also be used to facilitate multiplanar imaging of ultrasound-guided injections [11,12].…”
Section: Discussionmentioning
confidence: 99%